Analysis of muscle strength and endurance in healthy young adults and association of muscle strength with muscle endurance - Bhattacharjya, Jolly; Baishya, Reeta; Dutta, Bijit (International Journal of Research in Medical Sciences, 2019)
Background: Muscle strength has been studied as a predictor of general health and many diseases. Data on muscle strength of healthy adults are scarce in Assam. Aim of the study was to describe normative data for hand grip muscle strength and endurance among healthy young males and females of age group 18-21. Also, to find out any correlation between muscles strength and endurance. Methods: We have selected 79 healthy volunteers of both sexes of age group 18-21 years. We have measured muscle strength by hand grip dynamometer. Muscle endurance was calculated by asking the subjects to hold the dynamometer at one third of their muscle strength as long as they can. Results: In this study there were 46 males and 33 females. Mean muscle strength among the males is 27.09(SD7.05) and among the females is 10.76(SD6.19). Similarly mean endurance among males is 41.78(SD31.72) and among females is 16.15(SD9.81). These higher values of muscle strength and endurance in males are statistically significant. We have also found positive correlation between muscle strength and endurance in both the sexes. Conclusions: In this study we have seen that muscle strength and endurance of healthy young males are more than that of females. And also, muscle endurance increases with increase in muscle strength.